Outbreak of acute respiratory infection among infants in Lisbon, Portugal, caused by human adenovirus serotype 3 and a new 7/3 recombinant strain - Rebelo-de-Andrade, H (2011)
Human adenoviruses (AdVs) typically cause mild illnesses in otherwise healthy hosts. We investigated a pediatric outbreak of acute respiratory infection with fatal outcomes that occurred in Lisbon, Portugal, in 2004. Biological specimens were collected from 83 children attending two nurseries, a kinesiotherapy clinic, and the household of a nanny. Adenovirus infection was confirmed in 48 children by PCR and virus isolation. Most (96%) isolates were classified as being of subspecies B1. Phylogenetic analysis of fiber and hexon gene sequences revealed that most infants were infected with AdV serotype 3 (AdV3) strains. Infants attending one nursery harbored a new recombinant strain containing an AdV serotype 7 hexon and serotype 3 fiber (AdV7/3). Both the AdV3 and the AdV7/3 strains caused fatal infections. Two different serotype 3 strains were circulating in Lisbon in 2004, and the new AdV7/3 recombinant type originated from only one of those strains. These results demonstrate that recombination leads to the emergence of new adenovirus strains with epidemic and lethal potential.